COMPETITION STRATEGIES AND THEIR ROLE IN THE EXPANSION OF ENTERPRISES INTO INDUSTRY MARKETS - PANCHENKO, Volodymyr; KIBLYK, Andrii (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The study revealed the relevance of the problem of adopting, forming and implementing a competition strategy for the further successful expansion of enterprises (their products) in new markets.The purpose of the study was to improve the theoretical, methodological and applied principles of the formation and implementation of enterprise competition strategies in order to implement the effective expansion of their products on the markets, taking into account the industry specifics of the state of competitiveness and competition on them.The key questions that need to be answered before forming a business entity's strategy in the field of economic competition have been identified. A matrix was developed: "level of competition on the market - financial and economic capabilities of the business" and positioning of various types of competitive strategies of the enterprise was carried out on it. 9 types of competitive strategies are offered – offer unification, intensive capture, extensive promotion, inclusion of offer elements, diversification of the marketing mix, contrast of advantages, market development, partnership in expansion, total absorption - which can be chosen by business entities for expansion into different types of markets with different financial and economic opportunities . 4 types of competitors (alternative to competitive struggle) are defined: marketing prodigies, investment titans, unrealized giants, promising startups.The scientific novelty of the research results lies in the further development of the method of forming marketing strategies in the field of economic competition and the expansion of the company's products to new markets.The practical implication of the research results is that different anchoring alternatives in the market have varying degrees of difficulty, but nothing is impossible. As the financial and economic capabilities of the enterprise weaken, but for positioning in more competitive markets, the applied elements of the marketing complex should become more innovative, sophisticated and effective.
Keywords: competitive strategies; economic competition; competitiveness of enterprises; methodology; types of economic activity